O Processo SAAL e a arquitectura no 25 de abril de 1974 - José António Bandeirinha (Arquitetura, 2007)
The Local Ambulatory Support Service (SAAL) was set up to provide support for people living in substandard conditions. It was designed to be a decentralized service which built new homes and infrastructures in run-down neighbourhoods, using the design and technical support of the brigades that operated in them. Considered a coherent form of revolutionary form of architecture ("25th April Architecture"), this became one of the most discussed and referenced periods of our recent architectural history due to the prompt response by architects and other members of the planning team, unusual methodologies used and the quality of many of the buildings constructed. This abundant architectural output, till now only broached in partial studies, is systematically catalogued and analysed in this book.